Turtles and ice: winter activity in non-native turtles in Romania - Oana Iftime; Alexandru Iftime (Herpetozoa, 2025)
We present records of winter activity of non-native turtles, especially Trachemys scripta, the most common alien turtle in Romania. This species was observed basking in urban park lake settings in the winter months at the beginning of 2024. Trachemys scripta individuals were active during atypically warm days, but not during alternating cold spells with snowfall and ice formation; on warm days, turtles were also observed in the proximity of persisting lake ice. Other aquatic turtle species emerged from hibernation at the end of the winter, when temperatures were considerably higher, nearing 20 °C.